Japan's Policy Towards Russia and Siberia 1925-1912 (Journal of the College of Basic Education, 2022)
Japan has witnessed a major shift in its relations with the outside world since the advent of the CommodoreAmerican Matthew Perry in 1853 there has been a series of stormy changes that brought it togetherIt produced a complete revolution in the basic principles upon which Japan relied in its foreign policy; WhateverThe mechanisms of formulating the Japanese foreign policy as the main factors that drive such a policy are my concernInternational reality and the national way of understanding that reality.Prior to 1853, Japan was in a state of complete political and strategic isolation; But she foundIt itself was threatened politically and economically by, which forced it to secure itself militarily and economically againstThe West canceled what is known as unequal treaties and decided to end its isolation and open up to the WestShe became his equal after a short time.